Preclinical and Clinical In Vitro In Vivo Correlation of an hGH Dextran Microsphere Formulation - Vlugt-Wensink, K. D. F.; de Vrueh, R.; Gresnigt, M. G.; Hoogerbrugge, C. M.; van Buul-Offers, S. C.; de Leede, L. G. J.; Sterkman, L. G. W.; Crommelin, D. J. A.; Hennink, W. E.; Verrijk, R. (Pharmaceutical research, 2007)
To investigate the in vitro in vivo correlation of a sustained release formulation for human growth hormone (hGH) based on hydroxyethyl methacrylated dextran (dex-HEMA) microspheres in Pit-1 deficient Snell dwarf mice and in healthy human volunteers. A hGH-loaded microsphere formulation was developed and tested in Snell dwarf mice (pharmacodynamic study) and in healthy human volunteers (pharmacokinetic study). Single subcutaneous administration of the microspheres in mice resulted in a good correlation between hGH released in vitro and in vivo effects for the hGH-loaded microsphere formulation similar to daily injected hGH indicating a retained bioactivity. Testing the microspheres in healthy volunteers showed an increase (over 7-8 days) in hGH serum concentrations (peak concentrations: 1-2.5 ng/ml). A good in vitro in vivo correlation was obtained between the measured and calculated (from in vitro release data) hGH serum concentrations. Moreover, an increased serum concentration of biomarkers (insulin-like growth factor-I (IGF-I), IGF binding protein-3 (IGFBP-3) was found again indicating that bioactive hGH was released from the microspheres. Good in vitro in vivo correlations were obtained for hGH-loaded dex-HEMA microspheres, which is an important advantage in predicting the effect of the controlled drug delivery product in a clinical situations.